Morphological study of synovial changes in two-stage reconstructions of the infected hip and knee arthroplasties - Gontarewicz, Arthur (BMJ Group, 2012)
OBJECTIVES: To study the morphological changes of the regenerating synovium in two-stage revision arthroplasty, which is the gold standard for treatment of periprosthetic joint infection. DESIGN: The authors analysed a series of synovial biopsies to examine morphological changes in healing periprosthetic tissues damaged by previous surgery and infection. METHODS: Synovial tissues from 19 patients (10 knees and 9 hips) who underwent a two-stage exchange surgery for periprosthetic infection were reviewed and correlated with clinical and laboratory findings. SETTING: Retrospective morphological study. PARTICIPANTS: Archival tissues from 19 two-stage revision arthroplasties in adult patients. RESULTS: Healing synovial tissue obtained at the reimplantation surgery showed characteristic layering: superficial fibrin exudate, immature richly vascularised granulation tissue and deeper maturing granulation tissue and fibrosis. Although increased neutrophil counts were found in the majority of cases, 2 of 19 cases showed dense infiltrates indicative of persistent infection, which correlated with positive microbiology in one case. One of the cases failed due to acetabular loosening and two cases failed due to late superinfection. One case showed a dense infiltration of eosinophils suggestive of a hypersensitivity reaction, which was subsequently proven by cutaneous tests. Foci of extramedullary haematopoiesis were detected in two cases. CONCLUSIONS: We observed characteristic morphological changes in the healing synovial tissue during reimplantation surgery for periprosthetic infection in serologically and microbiologically sterile tissues. Substantial increased counts of synovial neutrophils (>200 cells/10 high-power fields) seem to be indicative of persistent infection of the joint; therefore, prolonged antibiotic therapy should be considered in positive cases.